A simple alternative method for the purification of Citrus tristeza virus - Mehmet Asil Yilmaz; Muharrem Arap Kamberoglu; Selma Ozturk (Phytopathologia Mediterranea, 2001)
A simple method for the purification of Citrus tristeza virus is described, based on virus extraction from liquid-nitrogen frozen midribs and cortical tissue of infected Mexican lime, precipitation with polyethylene glicol mol. wt 6000 (PEG 6000) column chromatography on Sephacryl S-300-HR columns, and concentration of viruscontaining fractions by PEG 6000, followed by low-speed (17,200 g) centrifugation. Virus preparations were satisfactorily clean, and were successfully used for the production of an antiserum which is now being evaluated.